Youth and Pop Culture in Indonesian Islam - Saluz, Claudia Nef (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This article presents a picture of Indonesian pop culture which I believe transmits both a sense of complexity and of the detailed interrelations among its forms. As it has been shown, each element in the kaleidoscope has its own distinctive characteristics, styles and manners. In the different ways Islam is contemporarily expressed and lived, a hybridization process is reflected that shows the challenges Indonesian Muslims face in integrating, rejecting or adapting glob- al influences from the western world as well as from the Islamic Middle Eastern countries. The example of the trendy veil shows how these global influences are integrated in locality and how locality is assimilated with global trends.DOI: 10.15408/sdi.v16i2.481